Eremiti e mendicanti: Sulle tracce dei frati di Brettino prima della "magna unio" - Bartolacci, Francesca (Quaderni di storia religiosa medievale, 2025)
Using the limited information available, this paper aims at reconstructing the events that characterised the history of the Hermits of Brettino from the early 13th century until 1256, when they became part of the Order of Hermits of St. Augustine. The Hermits of Brettino, named after the location of their first "eremo" in the northern Marche region, are one of the least known components of the "magna unio". Historiography has attributed to them a firm fidelity to their original hermitism throughout their entire existence. This paper, however, on the basis of the few available sources, challenges this stereotypical view, revealing instead an order that was continuously evolving institutionally. At one point in its history it also adopted mendicant practices, therefore competing with the Friars Minor.